Shoring up the ‘home guard’? Reflections on the development and deployment of police support volunteer programmes in England and Wales - Bullock, Karen (Policing and society, 2017)
Whilst as a branch of the extended police family they are under-researched, volunteers have long played a role within constabularies. However, in the context of dominant political ideologies which have called for citizens to be more active in crime control and, more prosaically, pressure on police budgets at a time of state contraction, the volunteer is becoming more visible both in policing policy discourse and in practice. A novelty within Anglo-Welsh policing, this article explores the development and deployment of police support volunteer (PSV) programmes. First, it examines the nature of the roles that PSVs play and how these relate to roles played by other actors in the organisation. Second, it explores aspects of their management focusing on their coordination, training and supervision. Third, it considers the degree to which PSVs are integrated into the organisation and accepted by other actors who work therein, and discusses the reasons why the promulgation of PSVs might be resisted by salaried staff. Lastly, the article considers the implications in light of the scholarship on the pluralisation of policing focusing on the interlinked themes of effectiveness, coordination and integration and regulation and accountability.